East Central Kansas Experiment Field: Field Station Weather Reports: 2023 Growing Season - Eric Adee (Kansas Agricultural Experiment Station Research Reports, 2024)
This report includes the annual summary of precipitation and temperatures from 2023 at the research locations represented in the 2024 Field Research Report and further details about the east central Kansas location.
Keywords: East Central Kansas; Kansas State experiment field; 2023 growing season weather; Kansas weather